Early Childhood Education Fund Financing Through a Managerial Approach for Sustainability and Quality of Education - Aqillah Nuhaa Widayawan; Alia Putri; Sisil Mukhtia; Suhardi Suhardi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine the management of funds in PAUD institutions from a managerial perspective. The method used is a literature study from various relevant sources over the past ten years. The results of the study indicate that the main sources of funds come from the government and the community, but limited funds and uneven distribution are the main obstacles. The principles of transparency, accountability, and effectiveness and efficiency must be applied in fund management so that the sustainability and quality of PAUD services can be maintained. The implementation of an open reporting system and stakeholder participation are also important to improve financial management performance. This study is expected to provide benefits for PAUD managers and can be used as a reference in developing more effective and sustainable fund management policies to improve the quality of early childhood education.